Glofitamab for Relapsed or Refractory Diffuse Large B-Cell Lymphoma - Dickinson, Michael J; Carlo-Stella, Carmelo; Morschhauser, Franck; Bachy, Emmanuel; Corradini, Paolo; Iacoboni, Gloria; Khan, Cyrus; Wróbel, Tomasz; Offner, Fritz; Trněný, Marek; Wu, Shang-Ju; Cartron, Guillaume; et al. (The New England journal of medicine, 2022)
BACKGROUND: The prognosis for patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL) is poor. Glofitamab is a bispecific antibody that recruits T cells to tumor cells. METHODS: In the phase 2 part of a phase 1-2 study, we enrolled patients with relapsed or refractory DLBCL who had received at least two lines of therapy previously. Patients received pretreatment with obinutuzumab to mitigate cytokine release syndrome, followed by fixed-duration glofitamab monotherapy (12 cycles total). The primary end point was complete response according to assessment by an independent review committee. Key secondary end points included duration of response, survival, and safety. RESULTS: Of the 155 patients who were enrolled, 154 received at least one dose of any study treatment (obinutuzumab or glofitamab). At a median follow-up of 12.6 months, 39% (95% confidence interval [CI], 32 to 48) of the patients had a complete response according to independent review. Results were consistent among the 52 patients who had previously received chimeric antigen receptor T-cell therapy (35% of whom had a complete response). The median time to a complete response was 42 days (95% CI, 42 to 44). The majority (78%) of complete responses were ongoing at 12 months. The 12-month progression-free survival was 37% (95% CI, 28 to 46). Discontinuation of glofitamab due to adverse events occurred in 9% of the patients. The most common adverse event was cytokine release syndrome (in 63% of the patients). Adverse events of grade 3 or higher occurred in 62% of the patients, with grade 3 or higher cytokine release syndrome in 4% and grade 3 or higher neurologic events in 3%. CONCLUSIONS: Glofitamab therapy was effective for DLBCL. More than half the patients had an adverse event of grade 3 or 4. (Funded by F. Hoffmann-La Roche; ClinicalTrials.gov number, NCT03075696.).
Keywords: difúzní velkobuněčný B-lymfom; Antibodies, Bispecific; Cytokine Release Syndrome; syndrom uvolnění cytokinů; nehodgkinský lymfom; Lymphoma, Non-Hodgkin; Humans; Neoplasm Recurrence, Local; lokální recidiva nádoru; protilátky bispecifické; Lymphoma, Large B-Cell, Diffuse; lidé